(untitled) - Abbas, Abul K. (Philadelphia, P.A., 2004)
The 2nd of this popular text emphasizes the fundamental concepts and principles of human immunology that students need to know, without overwhelming them with extraneous material. It leads the reader to a firm understanding of basic principles, using full-color illustrations; short, easy-to-read chapters; color tables that summarize key information clinical cases; and much more-all in a conveniently sized volume that's easy to carry. The New Edition has been thoroughly updated to reflect the many advances that are expanding our understanding of the field.
Keywords: Immunology,Immunity,Immunologic diseases